2012
DOI: 10.1016/j.devcel.2012.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Notch Ligand Endocytosis Generates Mechanical Pulling Force Dependent on Dynamin, Epsins, and Actin

Abstract: SUMMARY Notch signaling induced by cell surface ligands is critical to development and maintenance of many eukaryotic organisms. Notch and its ligands are integral membrane proteins that facilitate direct cell-cell interactions to activate Notch proteolysis and release the intracellular domain that directs Notch-specific cellular responses. Genetic studies suggest Notch ligands require endocytosis, ubiquitylation and epsin endocytic adaptors to activate signaling, yet the exact role ligand endocytosis serves r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
198
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 215 publications
(213 citation statements)
references
References 60 publications
9
198
2
Order By: Relevance
“…S2G). During active signaling, Notch transendocytosis has been proposed to create a force on the receptor, known as the "pulling force," which is thought to reveal the cleavage site and promote receptor activation (42). A recent publication demonstrated that ligandmediated NECD transendocytosis during signal activation is mechanistically distinct from steady-state ligand endocytosis (55).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…S2G). During active signaling, Notch transendocytosis has been proposed to create a force on the receptor, known as the "pulling force," which is thought to reveal the cleavage site and promote receptor activation (42). A recent publication demonstrated that ligandmediated NECD transendocytosis during signal activation is mechanistically distinct from steady-state ligand endocytosis (55).…”
Section: Resultsmentioning
confidence: 99%
“…Vimentin interacts with membrane-tethered proteins through PDZ motifs (48) and Jagged and Dll carry distinct PDZ sequences in their ICDs (49)(50)(51). Whereas the ECDs are important for receptor binding, the ICDs play important roles in signal activation through posttranslational modifications (37,52) and interactions with endocytic regulators (41)(42)(43). To elucidate whether the ICDs of Dll4 and Jagged 1 influence vimentin binding and Notch signaling, we swapped the ICDs of Dll4 and Jagged 1 (53) to generate the chimeric variants: JaggedECDDll4ICD and Dll4ECDJaggedICD.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations